Hydraulic optimization of the physical parameters of a drinking water distribution system (2021)
Drinking-water distribution systems are generally designed with methodologies based on trial-and-error tests, which generate feasible results. However, these trials are not the most economical and reliable solution since they do not consider the optimization of the network. For the present work, the hydraulic model of the drinking water distribution network of San José de Cúcuta, Colombia, was optimized by applying the concept of resilience rate and minimum cost. The development of the work consisted of the hydraulic modeling of the physical components of the network in EPANET software, as well as the application of calculations of the connectivity coefficient and the unitary power of each section. With the data obtained from the modeling and calculations, the physical parameters were optimized, and the cost-benefit ratio was estimated. It was found that the current drinking water distribution system does not have a power surplus to overcome a system failure. The optimization increased the total energy surplus of the network (261%) and the resilience rate (585%). Also, the connectivity coefficient was improved with an average value of 0.95. The hydraulic optimization methodology applied resulted in a network resilient to system failures.